Approaches To Youth Social Responsibility in Western Philosophy - Sultanov Ogabek Sultan ugli (Periodica Journal, 2024)
This study aims to study the methods of approach to social responsibility of youth in Western philosophy. Formation of social responsibility of young people is important within the framework of Western philosophy, and several main approaches have been developed in this regard. Deontological, utilitarian and existentialist approaches are analyzed in the research. The deontological approach encourages young people to assume social responsibility based on moral obligations and tasks. In this approach, it is emphasized the importance of young people to be formed as responsible individuals, following the moral rules and norms of society. Utilitarianism is based on directing social responsibility to the common welfare. In this approach, young people are encouraged to conduct their activities in a way that is designed for the benefit of others. It is noted that the decisions made by young people can affect the lives of many people, and therefore the need for actions to serve the interests of society is emphasized. The existentialist approach calls on young people to exercise social responsibility, focusing on issues of personal freedom and responsibility
Keywords: Aristotle; “Ahloqi Kabir”; Thomas Hobbes